Ethnic differences in primary care management of diabetes and cardiovascular disease in people with serious mental illness - Mathur, Rohini (Royal College of General Practitioners, 2012)
BACKGROUND: Patients with serious mental illness (SMI) have high rates of cardiovascular disease (CVD). In contrast to widespread perception, their access to effective chronic disease management is as high as for the general population. However, previous studies have not included analysis by ethnicity. AIM: To identify differences in CVD and diabetes management, by ethnicity, among people with SMI. DESIGN AND SETTING: Three inner east London primary care trusts with an ethnically diverse and socially deprived population. Data were obtained from 147 of 151 general practices. METHOD: Coded demographic and clinical data were obtained from GP electronic health records using EMIS Web. The sample used was the GP registered population on diabetes or CVD registers (52 620); of these, 1223 also had SMI. RESULTS: The population prevalence of CVD and diabetes is 7.2%; this rises to 18% among those with SMI. People with SMI and CVD or diabetes were found to be as likely to achieve clinical targets as those without SMI. Blood pressure control was significantly better in people with SMI; however, they were more likely to smoke and have a body mass index above 30 kg/m(2). Ethnic differences in care were identified, with south Asian individuals achieving better cholesterol control and black African or Caribbean groups achieving poorer blood pressure control. CONCLUSION: Risk factor management for those with SMI shows better control of blood pressure and glycosylated haemoglobin than the general population. However, smoking and obesity rates remain high and should be the target of public health programmes. Ethnic differences in management mirror those in the general population. Ethnic monitoring for vulnerable groups provides evidence to support schemes to reduce health inequalities.